2020
DOI: 10.3892/mco.2020.2004
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for secondary carcinoma in head and neck cancer patients following curative therapy: A retrospective clinical study

Abstract: Patients with head and neck squamous cell carcinoma (HNSCC) are at risk for local and regional relapse, as well as for occurrence of synchronous or metachronous secondary carcinoma. The aim of this retrospective study was to evaluate the frequency of secondary malignancies amongst HNSCC patients and their association with age, sex and TNM classification, as well as smoking and alcohol abuse. Data from 394 patients with HNSCC who were treated at the Department of Otorhinolaryngology-Head and Neck Surgery of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
8
0
2
Order By: Relevance
“…Leon (2009) demonstrated that continuing to smoke and drink alcohol after treatment increased the risk of developing a second malignancy by approximately three to five times, not only for oral cavity tumors but also for tumors affecting the entire upper gastrointestinal tract [ 9 ]. As a result, it is recommended that long-term follow-up of patients with oral cavity cancer who have undergone radical treatment and have abstained from alcohol and tobacco completely can improve survival [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leon (2009) demonstrated that continuing to smoke and drink alcohol after treatment increased the risk of developing a second malignancy by approximately three to five times, not only for oral cavity tumors but also for tumors affecting the entire upper gastrointestinal tract [ 9 ]. As a result, it is recommended that long-term follow-up of patients with oral cavity cancer who have undergone radical treatment and have abstained from alcohol and tobacco completely can improve survival [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that late clinical nodal stage, larger lymph node sizes, lymph node metastasis to level I–III, late combined stage, and late pathologic T stage all contributed to SPC occurrence in HNC survivors. Kuhlin B et al demonstrated that primary tumor localization, age, sex, or TNM classification were not identified as significant indicators of the secondary carcinoma occurrence in 394 cases [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In another large trial by Ping et al with 1512 patients of head and neck carcinoma treated with curative radiotherapy and Kuhln et al following curative treatment the reported incidence of SPM was 9% and 10.3% respectively. 17,18 Our study has taken only surgical candidates of malignancy hypopharynx and larynx following curative treatment and the incidence of SPM was 3.1%. All the candidates were of advanced stage (stage III and IV) requiring multimodality treatment.…”
Section: Monoclonal Modelmentioning
confidence: 99%